Production of a novel poly(ɛ-caprolactone)-methylcellulose electrospun wound dressing by incorporating bioactive glass and Manuka honey - Schuhladen, Katharina; Vakamulla Raghu, Swathi Naidu; Liverani, Liliana; Neščáková, Zuzana; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2020)
Wound dressings produced by electrospinning exhibit a fibrous structure close to the one of the extracellular matrix of the skin. In this article, electrospinning was used to fabricate fiber mats based on the well-known biopolymers poly(ɛ-caprolactone) (PCL) and methylcellulose (MC) using benign solvents. The blend fiber mats were cross-linked using Manuka honey and additionally used as a biodegradable platform to deliver bioactive glass particles. It was hypothesized that a dual therapeutic effect can be achieved by combining Manuka honey and bioactive glass. Morphological and chemical examinations confirmed the successful production of submicrometric PCL-MC fiber mats containing Manuka honey and bioactive glass particles. The multifunctional fiber mats exhibited improved wettability and suitable mechanical properties (ultimate tensile strength of 3–5 MPa). By performing dissolution tests using simulated body fluid, the improved bioactivity of the fiber mats by the addition of bioactive glass was confirmed. Additionally, cell biology tests using human dermal fibroblasts and human keratinocytes-like HaCaT cells showed the potential of the fabricated composite fiber mats to be used as wound dressing, specially due to the ability to support wound closure influenced by the presence of bioactive glass. Moreover, based on the results of the antibacterial tests, it is apparent that an optimization of the electrospun fiber mats is required to develop suitable wound dressing for the treatment of infected wounds.
CRIS-Team Scopus Importer:2020-07-31
Keywords: bioactive glass; electrospinning; Manuka honey; methylcellulose; wound healing